The incidence of fractures following bariatric surgery: A systematic review. (2018) - Marcil, Gabriel; Bourget-Murray, Jonathan; Shinde, Siddharth; Switzer, Noah; Debru, Estifanos; Church, Neal; Mitchell, Philip; Reso, Artan; Gill, Richdeep S.
Abstract: Introduction: The effects of bariatric surgery on improvement of the metabolic syndrome is well-described, but its effect on intrinsic bone fragility and fracture propagation is unclear. Therefore, the aims of this systematic review of the literature were to examine (1) the incidence of fracture following bariatric surgery, (2) the association of fracture with the specific bariatric surgical procedure, and (3) site-specific types of fractures associated with bariatric surgery. Methods: A comprehensive literature search was conducted through Medline, Embase, Scopus, Web of Science, Dare, Cochrane library, and HTA database. The search terms used were gastric bypass, sleeve gastrectomy and fracture. Results: Eight studies were included ( n  = 42, 567 patients). This included no randomized controlled trials. The average patient age was 43.3 years and 24.9% of patients were male. The average follow-up time was 3.7 years. 1960 patients had at least one fracture, and the total number of fractures encountered was 2326. Overall, 4.6% of patients who underwent bariatric surgery suffered from a fracture post-operatively. The operation associated with the greatest risk of fractures post-operatively was following a biliopancreatic diversion (10.66%), followed by restrictive procedures such as adjustable gastric band and sleeve gastrectomy (5.71%), with the Roux-en-Y gastric bypass having the lowest risk (2.66%). Of the fractures encountered, 1458 (63.08%) were of the lower extremity and pelvis and 763 (33.01%) were of the upper extremity. Only 90 (3.89%) axial skeleton fractures were reported. Conclusions: The overall risk of sustaining a fracture of any type after undergoing bariatric surgery is approximately 5 percent after an average follow up of 3.7 years. The greatest risk of fractures is associated with the biliopancreatic diversion surgery, with the Roux-en-Y gastric bypass being the most favorable. Fractures following bariatric surgeries tend to occur mostly in the lower extremity and pelvis. Highlights: The effect of bariatric surgery on intrinsic bone fragility and fracture propagation is unclear. This systematic review examines the incidence of fracture following bariatric surgery. 4.6% of patients who underwent bariatric surgery suffered from a fracture post-operatively. The greatest risk of fractures was associated with the Biliopancreatic Diversion. Fractures following bariatric surgeries tend to be at the lower extremity and pelvis.